2017
DOI: 10.1080/10790268.2017.1369217
|View full text |Cite
|
Sign up to set email alerts
|

The effects of semi-immersive virtual reality therapy on standing balance and upright mobility function in individuals with chronic incomplete spinal cord injury: A preliminary study

Abstract: This study is the first to assess the effects of semi-immersive VR therapy for patients with chronic iSCI and limited functional abilities. These results indicated that semi-immersive VR therapy has a positive effect and is a useful intervention for standing balance and upright mobility function in patients with chronic iSCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 34 publications
(43 reference statements)
0
41
0
Order By: Relevance
“…Regarding the intervention protocols, all the studies analyzed the effects of VR interventions through different technological devices compared to CPT. In terms of VR systems, most studies used the Nintendo Wii videogame console [ 22 , 38 , 44 , 45 ], video-capture systems [ 46 , 47 ], and VR-augmented therapy [ 39 , 41 , 42 ]. Another study [ 40 ] employed a VR system similar to the Nintendo Wii, based on force plates, and, finally, the last study [ 37 ] used the PlayStation 2 videogame console.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the intervention protocols, all the studies analyzed the effects of VR interventions through different technological devices compared to CPT. In terms of VR systems, most studies used the Nintendo Wii videogame console [ 22 , 38 , 44 , 45 ], video-capture systems [ 46 , 47 ], and VR-augmented therapy [ 39 , 41 , 42 ]. Another study [ 40 ] employed a VR system similar to the Nintendo Wii, based on force plates, and, finally, the last study [ 37 ] used the PlayStation 2 videogame console.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the different deficits treated, all the studies focused on their interventions to recover balance in patients with SCI. Specifically, four studies [ 37 , 38 , 43 , 44 ] analyzed the effects of VR interventions on sitting balance, while the remaining studies [ 22 , 39 , 40 , 41 , 42 , 45 , 46 , 47 ] focused on their interventions for recovering standing balance. In addition, most studies analyzed the effects of VR therapy in gait [ 39 , 41 , 42 , 45 , 47 ], and functional performance [ 22 , 37 , 39 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies reported effect sizes, which ranged from low to large treatment effects (Cohen's d values ranged from 0.41 to 1.95 and eta-squared values from 0.11 to 0.95) [33, 34, 39]. In addition, statistically significant long-term effects were observed on motor function [13, 14, 16, 31, 32, 3537, 39], balance [14, 31, 35, 36], and pain [14, 34].…”
Section: Resultsmentioning
confidence: 99%
“…All studies had design limitations (see Risk of Bias) and hence restriction on internal or external validity. Most of the studies did not perform randomization [13, 14, 16, 17, 19, 20, 22, 26, 2932, 36, 37] or blinding [10, 1317, 19, 22, 26, 28–32, 34, 36, 37].…”
Section: Resultsmentioning
confidence: 99%